2013
DOI: 10.1186/2193-1801-2-679
|View full text |Cite
|
Sign up to set email alerts
|

Cystadenocarcinoma of the parotid: case report of a BRAF inhibitor treatment

Abstract: BackgroundMutations of the proto-oncogene BRAF have been described in many cancers. Mutated BRAF causes overactive downstream signaling via MEK and ERK leading to excessive cell proliferation and survival. Their identification is of real interest because specific inhibitors have been developed.Methods and resultsWe report the case of a patient with an aggressive cystadenocarcinoma of the parotid with synchronous metastases. Cisplatine/5FU chemotherapy associated with palliative radiation therapy was used first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…In addition, cases showing distant metastases such as lung and bone metastases have been reported (3). While various chemotherapies are used for advanced SGCs and their efficacy may be dependent on histological type, overall, the results are unsatisfactory and there have been no reports of significant tumor responses to systemic chemotherapies in advanced cystadenocarcinoma (1,(11)(12)(13). Programmed death ligand 1 (PD-L1) expression in SGC tumor cells is frequently observed, indicating that it may play an important role in the immune tolerance and progression of SGC (14).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, cases showing distant metastases such as lung and bone metastases have been reported (3). While various chemotherapies are used for advanced SGCs and their efficacy may be dependent on histological type, overall, the results are unsatisfactory and there have been no reports of significant tumor responses to systemic chemotherapies in advanced cystadenocarcinoma (1,(11)(12)(13). Programmed death ligand 1 (PD-L1) expression in SGC tumor cells is frequently observed, indicating that it may play an important role in the immune tolerance and progression of SGC (14).…”
Section: Discussionmentioning
confidence: 99%
“…A prior case report described the use of vemurafenib alone after disease progression occurred during treatment with combination 5-fluorouracil and cisplatin in a patient with BRAF V600E–mutated parotid cystadenocarcinoma. 25 Another case reported on a series of patients with SDC whose tumors were analyzed using targeted mutational analysis, and described in detail one patient who harbored a BRAF V600E mutation. 26 That patient experienced disease progression after definitive concurrent chemoradiotherapy with weekly carboplatin and paclitaxel, and again after salvage chemotherapy with cyclophosphamide and doxorubicin.…”
Section: Discussionmentioning
confidence: 99%
“…To date, the published literature contains only a few reports regarding genetic alteration of RAF mutations in salivary gland tumors . Nardi et al , using SNaPshot molecular profiling, identified a BRAF mutation in 7% (two of 27) of cases of salivary duct carcinoma (SDC).…”
Section: Discussionmentioning
confidence: 99%